2017
DOI: 10.1159/000477543
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of Spinosyn Biosynthetic Gene Cluster in <b><i>Streptomyces</i></b> Species Is Dependent on the Expression of Rhamnose Biosynthesis Genes

Abstract: Spinosyns are a group of macrolide insecticides produced by Saccharopolyspora spinosa. Although S. spinosa can be used for industrial-scale production of spinosyns, this might suffer from several limitations, mainly related to its long growth cycle, low fermentation biomass, and inefficient utilization of starch. It is crucial to generate a robust strain for further spinosyn production and the development of spinosyn derivatives. A BAC vector, containing the whole biosynthetic gene cluster for spinosyn (74 kb)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…erythraea ATCC 40137 (Huang et al, 2016); through substantial genetic engineering and mutagenesis, this heterologous expression system allowed spinosad production to reached a titer of 800 mg/L in the resulting Sac. erythraea strain, which is hundreds of times higher than those in Streptomyces hosts, including S. albus, S. coelicolor, and S. lividans (Huang et al, 2016;Tan et al, 2017;Zhao et al, 2017). These studies confirmed the suitability of Saccharopolyspora spp.…”
Section: Introductionsupporting
confidence: 60%
“…erythraea ATCC 40137 (Huang et al, 2016); through substantial genetic engineering and mutagenesis, this heterologous expression system allowed spinosad production to reached a titer of 800 mg/L in the resulting Sac. erythraea strain, which is hundreds of times higher than those in Streptomyces hosts, including S. albus, S. coelicolor, and S. lividans (Huang et al, 2016;Tan et al, 2017;Zhao et al, 2017). These studies confirmed the suitability of Saccharopolyspora spp.…”
Section: Introductionsupporting
confidence: 60%
“…The structure and biosynthesis of spinosyn analogues have been clearly described [4,33], and studies on the transformation of its gene clusters and the improvement of heterologous expression have been studied [7,34,35]; however, the metabolic situation in vivo is complex, and any slight metabolic disturbance will lead to complex changes, which may produce unintended consequences [11]. Therefore, the analysis of the genome characteristics of S. pogona and related regulatory proteins may help to understand their gene expression preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Chaoyi Song et al constructed a spinosyn artificial gene cluster grouped into 7 operons, each with a strong constitutive promoter, and compared with the original gene cluster, the artificial gene cluster resulted in a 328-fold enhanced spinosyn production in Streptomyces albus J1074 [6]. Analogously, Tan et al overexpressed three rate-limiting steps of the heterologous production of spinosyn, and the production of spinosyn was increased gradually and finally reached 1.46 mg/L, which was approximately 1000-fold higher than the level of spinosyn produced by the wild-type strain S. albus J1074 [7]. However, probably due to the complex genetic background and the native advantages of natural hosts, the heterologous production of spinosyn analogues usually falls short of expectations.…”
Section: Introductionmentioning
confidence: 99%
“…The spinosyn biosynthetic pathway has been introduced into S. lividans TK24 and S. coelicolor M145 and M1154 . However, heterologous biosynthesis of target compounds is just the starting point as the production of NPs is very low.…”
Section: Heterologous Biosynthesis Of Spinosad In Actinomycetesmentioning
confidence: 99%